Nusantara Islamic Education at Islamic Boarding Schools - Mustain, Zainul; Rahmat, Rahmat (Yayasan Pendidikan Bustanul Ulum Mojokerto, 2024)
Islam Nusantara as an Islamic concept unique to the archipelago has become an interesting topic of discussion among academics and observers of Islamic education because, at the beginning of its emergence, there were pros and cons. After all, it was felt that Islam Nusantara was a new religion, even though Islam Nusantara was not the result of cultural creation but was the teaching of Islam by Ahlussunnah Wal Jamaah as a whole. essential even though linguistically there are various debates. The purpose of writing this article is to present Islam Nusantara in the style of Islamic boarding schools, where Islamic boarding schools in this context are also educational institutions that give birth to the concept of Islam Nusantara so that from the results of academic discussions at Islamic boarding schools, Islam Nusantara can be well accepted by society in general. as an inevitability in the life of a nation with Islamic culture and religion. This research uses qualitative research with a literature study approach. Meanwhile, the results of this research obtained several recommendations regarding Nusantara Islam in Islamic boarding schools, namely, 1) It is considered important for Islamic boarding schools to preserve Indonesian Islamic education, 2) The model of Nusantara Islamic education in Islamic boarding schools, and 3) The role of government is needed in the formulation and implementation of Nusantara Islamic education in formal education.